2005
DOI: 10.1002/ejic.200500234
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Crystal‐Chemical Principle for the Pyrochlore Structure

Abstract: Phase equilibrium studies of the Bi-Zn-Nb-O system show that pyrochlore does not form at chemical compositions predicted by the traditional formula for this crystal structure, A 2 B 2 O 6 OЈ, where A denotes large (8-coordinated, e.g. Bi 3+ ) and B small (6-coordinated, e.g. Zn 2+, Nb 5+ ) cation sites. Instead, pyrochlore forms only at compositions with excess B cations which, surprisingly, occupy the large A-cation sites. Reports of similar behavior in other pyrochlores suggest a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 52 publications
5
101
2
Order By: Relevance
“…In addition to extensive compositional ranges, pyrochlores exhibit a remarkable variety of exploitable physical properties, hence the considerable technical importance of this class of solids. [29] Bi-Co-Nb-O pyrochlores have been previously reported to form at the stoichiometries Bi 2 Co 2/3 Nb 4/3 O 7 , [31] [32] however, under the conditions of the present study none of these compositions are included in the pyrochlore singlephase field: Composition Bi 2 Co 2/3 Nb 4/3 O 7 formed a three-phase mixture as described in Figure 1 Compositions, nominal formulas, and refined unit cell parameters for single-phase Bi-Co-Nb-O pyrochlores (all dull dark greenish gray in color) prepared in the present study are given in Table 1. [34] The trends in unit cell parameters show a strong dependence on Bi concentration.…”
Section: Phase Formationmentioning
confidence: 97%
“…In addition to extensive compositional ranges, pyrochlores exhibit a remarkable variety of exploitable physical properties, hence the considerable technical importance of this class of solids. [29] Bi-Co-Nb-O pyrochlores have been previously reported to form at the stoichiometries Bi 2 Co 2/3 Nb 4/3 O 7 , [31] [32] however, under the conditions of the present study none of these compositions are included in the pyrochlore singlephase field: Composition Bi 2 Co 2/3 Nb 4/3 O 7 formed a three-phase mixture as described in Figure 1 Compositions, nominal formulas, and refined unit cell parameters for single-phase Bi-Co-Nb-O pyrochlores (all dull dark greenish gray in color) prepared in the present study are given in Table 1. [34] The trends in unit cell parameters show a strong dependence on Bi concentration.…”
Section: Phase Formationmentioning
confidence: 97%
“…4,5 This disorder has been attributed to the active lone pair of the Bi cation 6 and appears in the infrared ͑IR͒ spectrum of BZN as additional modes from those predicted by the ideal pyrochlore structure. [7][8][9] The additional IR modes were also observed by Chen et al 7 in three other bismuth pyrochlores Bi 3/2 ZnTa 3/2 O 7 ͑BZT͒, Bi 3/2 MgNb 3/2 O 7 ͑BMN͒, and Bi 3/2 MgTa 3/2 O 7 ͑BMT͒.…”
Section: Introductionmentioning
confidence: 95%
“…Instead, pyrochlore compounds with lone-pair active A cations frequently accommodate the offcentering through incoherent, local displacements. Vanderah, Levin, and Lufaso [4] have recently demonstrated that the A 2 O 0 sublattice of the pyrochlore can tolerate a large degree of substitutional as well as displacive disorder on the A-cation site. Indeed for certain pyrochlore compositions, the phase becomes stable only when such substitutional disorder is present on the A-site [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vanderah, Levin, and Lufaso [4] have recently demonstrated that the A 2 O 0 sublattice of the pyrochlore can tolerate a large degree of substitutional as well as displacive disorder on the A-cation site. Indeed for certain pyrochlore compositions, the phase becomes stable only when such substitutional disorder is present on the A-site [4]. Local static disorder, rather than coherent distortions of the structure can be advantageous in device applications where structural phase transitions are contraindicated.…”
Section: Introductionmentioning
confidence: 99%